Summum bonum az európai könyvtárügyben? Az európai integráció és a könyvtárak jogi szabályozása - Sipos, Anna Magdolna (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
As a survey which was examining law regulations of public libraries led by UNESCO delegated Frank Gardner in the middle of 1960s pointed, the laws governing library's op-eration are similar in several countries of the European continent but at the same time they are also aligning to the national specialities. In the recent past European council and EBLIDA analysed the same in the standardizing Europe. This survey came to the same conclusion, but showed even more similarities. The study introduces the factors determin-ing the recent standardization processes of the Library case in Europe, line up the pros and contras against standard legal regulation and highlights similarity and diversity.